Revolutionizing Arabic Language Reading Skills Among Junior Islamic School Students via Innovative Digital Comic Learning Media - Novita, Diana; Almaida Fitra Hamdala (WISE Pendidikan Indonesia, 2023)
This research aims to investigate the efficacy of utilizing digital comic media to enhance Qira'ah proficiency among seventh-grade students at MTs AL-Hikmah Bandar Lampung. The study addresses the following research questions: 1) How does the development of digital comic media contribute to improving Qira'ah proficiency among seventh-grade students at MTs AL-Hikmah Bandar Lampung; 2) What is the feasibility assessment of the digital comic media in enhancing Qira'ah proficiency among class VII students at MTs AL-Hikmah Bandar Lampung; 3) How do students respond to the implementation of digital comic media to enhance Qira'ah proficiency at MTs AL-Hikmah Bandar Lampung. Employing a research and development (R&D) approach, this study follows the ADDIE development model encompassing Analysis, Design, Development, Implementation, and Evaluation stages. The research outcomes indicate the high feasibility of Arabic digital comic media, validated by media experts with a commendable assessment score of 94.1%, and material experts with a noteworthy score of 91%. Additionally, student responses to the digital comic media garnered an overall average percentage of 91%, demonstrating a favorable reception. Likewise, teacher assessments of the digital comic media received a 95.5% score, attesting to its positive utility in the learning process. In conclusion, the developed Arabic digital comic media holds great promise as an effective tool for enhancing Qira'ah proficiency in the learning activities.